Seserahan Dalam Perkawinan Masyarakat Adat Lampung - Agung Tri Nugroho (Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Delivery or delivery money is money given by the male to the prospective in-laws for marital needs with its positive and negative impacts. The negative impact of delivery money is seen when it is set at a high amount by the prospective in-laws to be paid, making it difficult to be met. Not a few also couples who want to establish a household are forced to postpone marriage because of the high amount of money that has been determined from the woman side. The research question in this paper is how the implementation of the practice of conducting delivery money in marriage customs in Lampung, is it true that the determination of very high sums of money influences the delay in marriage in the community and how the Islamic law views the delivery money which causes delays in marriage. By using field research methods, the data have been grouped into two forms, namely quantitative data and qualitative data. Quantitative data is the data of the results of the questionnaire while the qualitative data is the data of the results of interviews and observations. Then from the quantitative data tables are then analyzed and concluded while the qualitative data is connected between one fact and the other facts, then analyzed using a descriptive analysis approach. The results of the study found that the indigenous people of Lampung all practiced giving money and stipulated it by looking at the education of women, their work and the number of stipulated habits in the village, and eight pending marriages from several cases due to high cash, to the impacts arising from the stipulation of high and contradictory money with valid ‘urf terms; it can be concluded that the law of high passing money is not appropriate as it should apply. And many have charged men whose economies are middle to lower and who have dependents to carry out marriages resulting in delays in marriage.